2020
DOI: 10.1002/csc2.20256
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the searchability, breeding utility, and efficient management of germplasm accessions in the USDA−ARS rice collection

Abstract: Genebanks conserve worldwide crop genetic diversity in systematically assembled and maintained ex situ collections for use by plant breeders and geneticists to improve the productivity, value, and sustainability of agriculture. Challenges faced in genebank management include providing sufficient and accurate trait information to facilitate searching the collection; controlling redundant accessions, seed mixtures, and mislabeled accessions; and identifying gaps in diversity. To help address these issues, a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…We concluded four FNPs might contribute to the grain size difference between the two japonica subpopulations, namely, qLGY3_SNP, GW5_InDel, GLW7_InDel and GL7_InDel1, because the allele ratio is differentiated between the subpopulations (96%, 76%, 86% and 84% for allele 1 in Tej and 90%, 83%, 89% and 94% for allele 2 in Trj for four FNPs, respectively). This allele distribution might explain why Tej accessions have wider but shorter grains in contrast to Trj accessions as shown in previous studies (Ali et al 2011;McClung et al 2020;Zhao et al 2011).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We concluded four FNPs might contribute to the grain size difference between the two japonica subpopulations, namely, qLGY3_SNP, GW5_InDel, GLW7_InDel and GL7_InDel1, because the allele ratio is differentiated between the subpopulations (96%, 76%, 86% and 84% for allele 1 in Tej and 90%, 83%, 89% and 94% for allele 2 in Trj for four FNPs, respectively). This allele distribution might explain why Tej accessions have wider but shorter grains in contrast to Trj accessions as shown in previous studies (Ali et al 2011;McClung et al 2020;Zhao et al 2011).…”
Section: Discussionmentioning
confidence: 57%
“…In the future, it will be important to clarify the novel loci for these subspecies differences in segregating populations. Although there is a known close relationship between the aus and indica subpopulations composing the indica subspecies and similarly between temperate japonica (Tej) and tropical japonica (Trj) subpopulations composing the japonica subspecies, significant difference in grain size were noted between the Tej and Trj subpopulations, suggesting grain size is an important driver of subpopulation structure (Ali et al 2011;McClung et al 2020;Zhao et al 2011). To investigate this relationship, we used our data to compare the grain size traits of four subpopulations (Table S2 and Table S3), and found significant differences between the Tej and Trj subpopulations for all four grain size traits but no difference between the aus and indica subpopulations, consistent with the previous results from different locations.…”
Section: Discussionmentioning
confidence: 99%
“…The commercial check cultivars developed for production in the southern United States included ‘Mermentau’ (PI 665688), a long‐grain cultivar having 22.6% apparent amylose content and an alkali spreading value of 4.0 indicating an intermediate gelatinization temperature, which was released in 2012 (Oard et al., 2014), and ‘Titan’ (PI 680613), a medium‐grain cultivar having 15.0% apparent amylose content and an alkali spreading value of 7.0 indicating a low gelatinization temperature, which was released in 2017 (Sha et al., 2018). More recently, the aforementioned markers for grain quality (RM190, Wx In1 and Wx Ex6, and Alk ) confirmed that Mermentau had an intermediate amylose content and intermediate gelatinization temperature and Titan had a low amylose content and low gelatinization temperature (McClung et al., 2020). The study was conducted in a randomized complete block design with four replications.…”
Section: Methodsmentioning
confidence: 94%
“…Estrela (GSOR 301227) is a cultivar originating from Colombia that is an extra‐long grain with low amylose content and high gelatinization temperature based on marker alleles for RM190, Wx In1 and Wx Ex6, and Alk (Eizenga et al., 2014; McClung et al., 2020), it possesses the Pi‐z (Fjellstrom et al., 2006) and Pi‐ks (Fjellstrom et al., 2004) major genes for resistance to rice blast disease, and is pubescent. The NSFTV199 parent (GSOR 301190) is of unknown origin and is a medium grain with intermediate amylose content and intermediate gelatinization temperature based on marker alleles for these genes (Eizenga et al., 2014; McClung et al., 2020). The plant is glabrous, and it possesses the Pi‐ks rice blast resistance gene (Eizenga et al., 2014; Eizenga, Jia, et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Molecular markers play an important role in the identification and characterization of new germplasm (O'Neill et al., 2003), and simple sequence repeat (SSR) markers are often used to analyze the genetic diversity of rice. The ability of SSR markers to differentiate rice accessions genotypically is documented by the fact that a “fingerprint marker” panel consisting of 12 SSR markers differentiated a diverse subset of nearly 2,000 O. sativa accessions from the U.S. germplasm collection, and with two additional SSR markers, the identity of nearly 95 U.S. varieties that are closely related was ascertained (McClung et al., 2020). The rich genetic diversity found in common wild rice ( O. rufipogon ) accessions from Southeast Asia, mainly China, has been documented in several studies involving 90–4,173 accessions genotyped with 24–46 SSR markers (Li et al., 2010; Pan et al., 2018; Sun & Yang, 2009; Xue et al., 2016), confirming the ability of SSR markers to document the genetic diversity in this ancestral wild species.…”
Section: Introductionmentioning
confidence: 99%